Injuries and special concerns of female figure skaters - Lipetz, J.; Kruse, R. J. (Clinics in Sports Medicine, 2000)
Figure skaters are often young athletes involved in an extremely stressful, structured environment that is focused solely on skating. These athletes are at risk for a multitude of psychologic concerns, including poor communication skills, performance anxiety, stress, and family issues. Helping athletes develop self-awareness, techniques to control stress and anxiety, motivational strategies, ability to maintain concentration, and emotional balance is best done with the guidance of a sports-trained counseling professional. Communication among the athlete, parents, and coaches is extremely important. Often, coaches tell the athlete how and what to feel, and the athlete falls into a routine of trying to please coaches and parents instead of developing her own persona. The communication between pairs skaters and ice dancers is integral to their success. Excellent interpersonal skills among members of pair teams are advantageous in creating a lasting relationship. Honesty, respect, clarity, consistency, and sincerity are essential components of outstanding teammates and should be cultivated. On the other hand, sarcasm, disrespect, castigation, and ridicule should be addressed immediately and should be discouraged strongly. Clin Sports Med 2000 Apr;19(2):369-80